Identification of the Common Type of Pesticides Used by Bee Farmers from Selected Honey-Producing Areas in Tanzania: A Case of Kijiji Cha Nyuki Co. Ltd, Singida Region - Kachinde , Lucas (International Journal of Food Sciences, 2023)
Purpose: The main purpose of this study was to identify the common type of pesticides used by bee farmers. Specifically, the study presents preliminary findings of an inquiry that examined pesticides used by bee farmers and evaluates the awareness among farmers on the negative effects of pesticides in bee products from Kijiji cha Nyuki located in Tanzania. Methodology: A mixed methods approach was adopted for this study and collected data both primary and secondary data were collected using physical observation and survey, interviews, and questionnaires, purposive and random sampling techniques were used in this study to select a total of 104 participants who was taken as a sample from universal populations. Qualitative and quantitative data were analyzed using IBM Statistical Package for Social Sciences (SPSS) Computer Programme version 25, where the statistics aspect was determined from the results obtained from both questionnaires and laboratory experiments. A preliminary investigation from Africa's most renewed bee village in Tanzania; collected samples were analyzed at TBS & SGS laboratories. Findings: Based on the findings from informants comprises of two forest officers and two district agricultural officers showed despite a variety of pesticides that can contaminate bee and honey products, the widely observed are Insecticides (cynahalotrine, chlorpyrifos, clothianid), Fungicides (boscalid), and Herbicide (pendimethohele, and cyfluthrin). To mitigate the challenge posed by these pesticides, farmers always work hard to comply with pesticide regulations NBPIS, NBP, 1998, Beekeeping Act No. 15/2002; Beekeeping Regulations, 2005; NBP 2001-2010 and GCBP 2007. Unique Contribution to the Theory and Policy: the study suggests that participants should be guided to produce the expected outcome, and it has to start with the issue of power. In terms of the policy implementation process, the way policy regulating pesticides and policies activities are communicated should set the right tone that will encourage collaboration to ensure all participants will fully contribute. So, by paying attention to the effect of power, the fundamental principles of openness and inclusiveness can be upheld during the policy design and implementation process. It also recommends further study that will examine the perceptions of decision-makers, consumers, beekeepers, and academicians about the extended use of pesticides in Tanzania, bearing in mind the health implication of the unauthorized use of pesticides.